APAKAH LEVERAGE MAMPU MEMODERASI DAMPAK PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP STOCK RETURN? - arfian tanjung; Syarif M. Helmi; Khristina Yunita (Jurnal Riset Akuntansi, 2024)
This study aims to determine the effect of Return on Asset, Operating Profit Margin, Dividend Yield, and Dividend Payout Ratio on stock returns in non-cyclical consumer sector companies on the Indonesia Stock Exchange (IDX) in 2019-2023 and the ability of Leverage to moderate the impact of independent variables. The population in the study included 55 main board type non-cyclical consumer sector issuers on the Indonesia Stock Exchange (IDX). While the sample taken was 28 companies using purposive sampling technique. This study uses multiple linear regression, moderation regression, and hypothesis testing. The results of this study indicate that simultaneously Return on Asset, Operating Profit Margin, Dividend Yield and Dividend Payout have no significant effect on stock return. Partially the Return on Asset variable has a significant positive effect on stock return but the Operating Profit Margin, Dividend Yield, and Dividend Payout variables have an insignificant effect on stock return. Leverage as a moderating variable has not been able to moderate the impact of Return on Asset, Operating Profit Margin, Dividend Yield and Dividend Payout on stock return.